Procedural Justice and Relational Theory Empirical, Philosophical, and Legal Perspectives - Meyerson, Denise; Mackenzie, Catriona; MacDermott, Therese (Routledge Research in Legal Philosophy, 2021)
This book bridges a scholarly divide between empirical and normative theorizing about procedural justice in the context of relations of power between citizens and the state. Empirical research establishes that people's understanding of procedural justice is shaped by relational factors. A central premise of this volume is that this research is significant but needs to be complemented by normative theorizing that draws on relational theories of ethics and justice to explain the moral significance of procedures and make normative sense of people's concerns about relational factors. The chapters in Part 1 provide comprehensive reviews of empirical studies of procedural justice in policing, courts and prisons. Part 2 explores empirical and normative perspectives on procedural justice and legitimacy. Part 3 examines philosophical approaches to procedural justice. Part 4 considers the implications of a relational perspective for the design of procedures in a range of legal contexts. This collection will be of interest to a wide academic readership in philosophy, law, psychology and criminology.